1984
DOI: 10.1584/jpestics.9.471
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of the Herbicide Alloxydim-sodium in Soil

Abstract: Alloxydim-sodium (ADS), sodium salt of 2-(1-allyloxyaminobutylidene)-5, 5-dimethyl-4-(methoxycarbonyl)cyclohexane-l, 3-dione, 14C-labeled at butylidene-1 and ring-1, 5, respectively, was degraded with a half-life of about 5 days in Oiso soil at 25oC in the dark. The following were identified as degradation compounds by thin-layer cochromatography and mass spectrometry; deallyloxylated compound (I), two isomers of oxo-tetrahydrobenzoxazoles (II and III), deallyloxyaminated compound (VI), demethoxycarbonylated c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…Similar results were obtained for alloxydim when it was sprayed on several crops such as sugar beet or wild oat [38,51]. In unsterilized soil, the half-life of alloxydim was 5 to 6 days under dark incubation [52]. In this research, the evolution of 14 CO 2 was investigated as a measure of microorganism activity in the soil.…”
Section: Biotic Processessupporting
confidence: 69%
See 2 more Smart Citations
“…Similar results were obtained for alloxydim when it was sprayed on several crops such as sugar beet or wild oat [38,51]. In unsterilized soil, the half-life of alloxydim was 5 to 6 days under dark incubation [52]. In this research, the evolution of 14 CO 2 was investigated as a measure of microorganism activity in the soil.…”
Section: Biotic Processessupporting
confidence: 69%
“…Ono et al [52] also concluded that photolysis of alloxydim occurred when a soil spiked with an aqueous solution of this herbicide was exposed to sunlight.…”
Section: Photolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are several works that study alloxydim photodegradation in different conditions [10,11,21], its mechanism of photolysis is not well-known. involving these species are one of the most common routes of pesticide transformation.…”
Section: Structure Elucidation Of Phototransformation Products Degramentioning
confidence: 99%
“…Although it is known that this herbicide is easily degradated in different conditions there is little information in the literature on the fate of this compound in the environment [9][10][11].…”
Section: Introductionmentioning
confidence: 99%